Impact of a novel limbal-rigid contact lens on potential cost savings in Stevens-Johnson syndrome patients from postmarket surveillance - Kenichi Kimura; Mayumi Ueta; Hideki Fukuoka; Koji Kitazawa; Tsutomu Inatomi; Shigeru Kinoshita; Ryoichi Shiota; Naoki Yamauchi; Jiro Miyazaki; Satomi Sakabayashi; Satoshi Teramukai; Kojiro Imai; et al. (AJO International)
Purpose: To investigate the safety, efficacy, and potential-cost-savings of a newly-developed limbal-rigid contact lens (CL) via postmarket surveillance (PMS). Design: Postmarket prospective observational use-results surveillance with cost-savings analysis. Methods: We examined 80 eyes of 68 Stevens-Johnson syndrome (SJS) cases using the newly-developed Suncon Kyoto-CS limbal-rigid CL (Sun Contact Lens). CL-wear-associated best-corrected visual acuity (BCVA), objective signs (i.e., bulbar-conjunctival hyperemia, upper-eyelid conjunctival scarring, eye discharge, keratoconjunctival epithelial defect, corneal opacification, and corneal neovascularization), and subjective symptoms (i.e., dryness and eye pain) at baseline and at 6-months of CL use were measured and compared, with adverse events noted. Potential cost savings from improvements in CL-wear-related BCVA were estimated based on the potential for improvements in each patient's visual-impairment-grade under the Japanese Pharmaceuticals and Medical Devices Agency (PMDA) disability pension plan. Main outcome measures were potential cost savings via use of the CL. Secondary outcome measures were CL safety and efficacy via PMS. Results: At 6-months of CL use, the median BCVA in the CL-fitted eyes improved from 1.30 to 0.70 logMAR compared to that of spectacle correction at baseline (P < 0.001), and improvement of bulbar-conjunctival hyperemia, dryness, and eye pain was observed (P < 0.001, P < 0.001, and P < 0.001, respectively). No serious adverse events occurred. Potential-cost-savings analysis showed visual-impairment-grade improvement in 18 (28.6 %) of 63 patients. Considering the financial amount of the PMDA disability pension, estimated total potential cost savings was >6.9-million U.S. dollars. Conclusion: The newly-developed limbal-rigid CL was found safe and effective for treating SJS-associated ocular sequelae, and potentially reduces disability-pension costs.